2019
DOI: 10.18502/cmm.5.1.532
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-mycological profile of tinea capitis and its comparative response to griseofulvin versus terbinafine

Abstract: Background and Purpose: Tinea capitis is the most common superficial mycosis inchildren. This disease is a contagious infection with worldwide distribution and isoccasionally associated with permanent alopecia. The treatment of this infectionusually requires the administration of appropriate oral antifungal agents. The currentstudy was conducted to evaluate the clinico-mycological profile of tinea capitis andcompare the efficiency of oral griseofulvin and terbinafine in the treatment of thisdisease.Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
3
1
6
Order By: Relevance
“…(2019) [26] . reported that males responded better when treated with terbinafine and griseofulvin [27] , which is inconsistent with this study findings showing that dermatophyte clinical isolates from female responded better to griseofulvin and terbinafine. Another study in Nigeria reported terbinafine as the most active antifungal agent against dermatophytes [28] .…”
Section: Discussioncontrasting
confidence: 99%
“…(2019) [26] . reported that males responded better when treated with terbinafine and griseofulvin [27] , which is inconsistent with this study findings showing that dermatophyte clinical isolates from female responded better to griseofulvin and terbinafine. Another study in Nigeria reported terbinafine as the most active antifungal agent against dermatophytes [28] .…”
Section: Discussioncontrasting
confidence: 99%
“…The usual routes of infection of tinea capitis include chiefly animal-to-human and human-to-human transition and are usually enhanced by poor hygiene, overcrowding, lower socioeconomic status, and sharing contaminated fomites such as hats, brushes, pillows, and other inanimate objects. 2,3 Although tinea capitis affects predominantly pre-adolescent children with a peak occurrence between 3 and 7 years of age, [4][5][6][7] a study conducted by Ziegler et al 8 demonstrated a high prevalence rate of scalp ringworm in adults and the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…2) como una nueva familia para el tratamiento de la micosis superficial por dermatofitos y candidosis mucocutánea, ha demostrado utilidad en la terapia combinada de las micosis por mohos raros: Lomentospora prolificans, Scedosporium spp, Purpureocillium spp. y en feohifomicosis, con evidencia que sustenta el uso como monoterapia en el tratamiento de cromomicosis por Cladophialophora carrionii 20,37,38 . Inhibe la síntesis del ergosterol inactivando la escualeno epoxidasa, con la consecuente acumulación tóxica de escualeno (Fig.…”
Section: Alilaminas (Terbinafina Naftifina Butenafina)unclassified